2011
DOI: 10.1111/j.1574-6968.2010.02204.x
|View full text |Cite
|
Sign up to set email alerts
|

Transposition of Tn916  in the four replicons of the Butyrivibrio proteoclasticus B316T genome

Abstract: The rumen bacterium Butyrivibrio proteoclasticus B316(T) has a 4.4-Mb genome composed of four replicons (approximately 3.55 Mb, 361, 302 and 186 kb). Mutagenesis of B316(T) was performed with the broad host-range conjugative transposon Tn916 to screen for functionally important characteristics. The insertion sites of 123 mutants containing a single copy of Tn916 were identified and corresponded to 53 different insertion points, of which 18 (34.0%), representing 39 mutants (31.7%), were in ORFs and 12 were wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…All (except one) the streptococcal ICEs belonging to the Tn 916 family detected in this study encode a tyrosine integrase identical or almost identical to the Tn 916 integrase. Analyses of a high number of insertion sites in various hosts showed that Tn 916 , despite having a low specificity of integration, still has a preference for AT rich regions (consensus TTTTTnnnnnnAAAAA; Hosking et al, 1998 ; Cookson et al, 2011 ). Furthermore, the analyses of insertion sites after conjugal transfer to Butyrivibrio proteoclasticus B316 T , whose genome has a similar GC percent as the ones of Streptococci (39%), showed that only 34% of the 123 analyzed insertions disrupt annotated ORFs even if 90% of this genome is made of ORFs ( Cookson et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…All (except one) the streptococcal ICEs belonging to the Tn 916 family detected in this study encode a tyrosine integrase identical or almost identical to the Tn 916 integrase. Analyses of a high number of insertion sites in various hosts showed that Tn 916 , despite having a low specificity of integration, still has a preference for AT rich regions (consensus TTTTTnnnnnnAAAAA; Hosking et al, 1998 ; Cookson et al, 2011 ). Furthermore, the analyses of insertion sites after conjugal transfer to Butyrivibrio proteoclasticus B316 T , whose genome has a similar GC percent as the ones of Streptococci (39%), showed that only 34% of the 123 analyzed insertions disrupt annotated ORFs even if 90% of this genome is made of ORFs ( Cookson et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…If this happens the host will die, to get around this some mobile elements are site-specific or preferentially target inter-genic regions (Cookson et al, 2011). Also most transposable elements (including ICE) are tightly regulated so that they only transpose at low frequency or transpose when the bacteria are stressed, such as antibiotics in their environment (reviewed in Roberts and Mullany, 2009; Wozniak and Waldor, 2010).…”
Section: Mobile Genetic Elementsmentioning
confidence: 99%
“…Tn916 was stably maintained in the transconjugants following non-selective growth. We mapped the integration sites of three transconjugants of each species and identified three unique, frequently intergenic, AT-rich integration sites in each, as expected (Table S1) (Cookson et al, 2011;Mullany et al, 2012;Scott et al, 1994). Because Tn916 does not integrate in one defined chromosomal site, but instead within an AT-rich region that can be found in many places on a chromosome, Tn916 had the advantage in target site selection and thus stable acquisition during these matings.…”
Section: Detecting Stable Acquisition Of Conjugative Elements In Transconjugantsmentioning
confidence: 80%